Proximity of the mandibular anterior root apices to the buccal bone surface: A cone-beam computed tomographic study - Isha Gupta; Neeta Shetty; Junaid Ahmed; Kundabala Mala; Srikant Natarajan; Neetha J Shetty (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study is to evaluate the distance from the buccal cortical bone surface to the root apex in the anterior mandibular teeth using cone-beam computed tomography (CBCT) and to correlate it to various associated factors (tooth type, gender, and age). Materials and Methods: CBCT images of mandibular anterior teeth from 120 patient records with a sample size of 360 teeth were analyzed. The distance from the buccal bone surface to root apex and 3 mm above the root apex in the sagittal view was reconstructed using the Romexis software version 3.2.1. Results: Distances from the buccal cortical bone surface to the apices of the root and 3 mm from the apex of the root were greater at the mandibular canine region than the central and lateral incisor (P < 0.001). The buccal bone was significantly thicker corresponding to the apices of the teeth compared to the region 3 mm from the apex (P < 0.001) The mean distance value from the cortical buccal bone surface to the lateral incisor apex (4.03 mm) was significant more among females (P = 0.006). Furthermore, the measured distance at the root apex and 3 mm above the of the root apex of the mandibular anterior roots were significantly more in patients below the age of 40 years (P < 0.05). Conclusion: The distance from the buccal bone's surface to the apex and 3 mm from the apex in the mandibular anterior region is significantly affected by the tooth type and patients' age. CBCT is a reliable tool for presurgical evaluation for both these parameters during endodontic surgeries and implant placement.